Sense of Femininity in Ho Xuan Huong’s Poetry - Phạm, Văn Hóa (Open Access Library Journal, 2022)
“The queen of Nom poetry” in the late Le and early Nguyen Dynasty period, Ho Xuan Huong is the leading female poet of Vietnamese medieval literature. Her poetry presented a sense of femininity, protested against Feudal Confu cianism, and affirmed the personality and position of women in the society. Based on feminist theory, we would like to affirm the sense of femininity in Ho Xuan Huong’s poetry in the pursuit of a desire for self-chosen love, an equal and self-controlled marriage system, and autonomy in communication and composition. The article contributes to solving problems related to per ception of gender theory and the case of Ho Xuan Huong’s poetry. With what she has experienced in life, Ho Xuan Huong’s poetry expressed the sense of desire to hold her head up high in the very special male-dominated world. We believe that the sense of femininity in Ho Xuan Huong’s poetry has to a certain extent overturned the gender inequality of men and women in the Confucian society